(untitled) (Modern education and development, 2024)
Listening comprehension is an essential skill in language acquisition, and effective listening strategies can significantly enhance learners’ understanding and retention. This article explores the three primary stages of listening: pre-listening, while-listening, and post-listening, and examines how these stages contribute to better learning outcomes. The article discusses techniques and activities for each stage, highlighting their roles in preparing, engaging, and consolidating information. Additionally, the article reflects on the importance of contextualizing listening materials, the role of vocabulary, and the use of feedback to support learners throughout the listening process.